Drones - Murray, Julie, 1969- (2021)
Introduces readers to different types of drones and describes their features.
Drones -- How drones are used -- Military drones -- More facts.
"Level 3--transitional. More developed language and vocabulary for readers who are becoming more independent"-- Title page verso.
Includes index.
Ages 5-9
Keywords: Drone aircraft -- Juvenile literature; Drone aircraft; Drone aircraft; Juvenile works; Readers (Publications); Readers (Publications)